3.5 mm compliant robotic surgical forceps with 4 DOF : design and performance evaluation. (16th February 2023) - Bandara, D. S. V.; Nakadate, Ryu; Marinho, Murilo M.; Harada, Kanako; Mitsuishi, Mamoru; Arata, Jumpei
Abstract : Minimally invasive surgery (MIS) is a viable alternative to general surgery with distinct advantages. Robotically assisted MIS, has been demonstrated to achieve higher accuracy and repeatability in comparison with those of manual procedures. Despite these advantages, owing to the nature of some surgical procedures in which dexterous tissue manipulations in deep narrow areas of the human body are necessary, there is a need for further miniaturized tools with smaller bending radii. To cater to this requirement, this study proposes a new compliant mechanism based surgical robotic forceps. It can generate four degrees of freedom at the tip of the forceps including two bending motions in two perpendicular axes, grasping and rotation. A better combination of the stress distribution through the elastic material, grasping force, and range of motion was determined based on a series of finite element analyses. In addition, the manufactured prototype underwent a series of laboratory experiments to evaluate its effectiveness. Details of the mechanism, finite element analysis, prototype implementation, and evaluations are presented in this paper. GRAPHICAL ABSTRACT: UF0001